X-ray diffraction imaging of cardiac cells and tissue. (July 2019) - Nicolas, Jan-David; Bernhardt, Marten; Schlick, Susanne F.; Tiburcy, Malte; Zimmermann, Wolfram-Hubertus; Khan, Amara; Markus, Andrea; Alves, Frauke; Toischer, Karl; Salditt, Tim
Abstract: With the development of advanced focusing optics for x-rays, we can now use x-ray beams with spot sizes in the micro- or nanometer range to scan cells and large areas of tissues and continuously record the diffraction signals. From this data, x-ray scattering maps or so-called x-ray darkfield images are computed showing how different types of cells or regions of tissues differ in their diffraction intensity. At the same time a diffraction pattern is available for each scan point which encodes the local nanostructure, averaged over many contributing constituents illuminated by the beam. In this work we have exploited these new capabilities of scanning x-ray diffraction to investigate cardiac muscle cells as well as cardiac tissue. We give examples of how cardiac cells, especially living, cultured cells, can be prepared to be compatible with the instrumentation constraints of nano- or micro-diffraction instruments. Furthermore, we show how the developmental stage, ranging from neonatal to adult cells, as well as the final preparation state of the cardiomyocytes influences the recorded scattering signal and how these diffraction signals compare to the structure of a fully developed cardiac muscle.